Population dynamics of the White stork Ciconia ciconia in Slovenia between 1999 and 2010 - Denac, Damijan (Acrocephalus, 2010)
Between 1999 and 2010, an annual census of the White Stork Ciconia ciconia breeding population was carried out in Slovenia using standardised methods. The Stork's population was concenrrated in the NE and SE parts of Slovenia. Inthe 1999-2010 period, the breeding range of its population in Slovenia expanded in NW direction (the Savska ravan region), in SW direction (the Notranjsko podolje and Pivško podolje regions), but the speci es also colonized a part between Central and SE Slovenia (Dolenjsko podolje). Between 193 and 240 pairs were breeding during the study period, 209 pairs on average (HPa). The largest number of breeding pairs was recorded in 2004, the smallestin 2005. During the study period, breeding pairs (HPa) occupied 350 discrete nests in total. Average number ofbreeding pairs that raised juveniles(HPm) was 161. The highest fecundiry was recorded in 2004, when 534 juveniles (JZG) f!edged, the lowest in 2006, with only 219 f!edged juveniles. On average, 414 juveniles f!edged per year. The breeding pairs' (JZa) average breeding success in these 12 years was 2.02, the highest in 2000 (2.41), the lowest in 2006 (1.09). Average breeding success for the success ful breeding pairs (JZm) was 2.57. The highest was in 2007 (2.94), the lowest in 2006 (2.07). The largest number of breeding pairs in 2004 and 2008 can be eXplainedby the favourable fecundiry in the population in 2000 and 2004, as juveniles become sexually mature at the age of 3- 5 years, and at that age they generally return to the breeding grounds for the first time. The lowest number of breeding pairs and poor breeding success in 2005 and 2006 was causedby late arrival of White Storks to the breeding grounds and by unfavourable weather conditions during the breeding period. The pattern of nests placemenr did not change gene rally during the last 12 years. (Abstract truncated at 2000 characters)
Keywords: bela štorklja; Birds; Ecosystem; Ekosistem; gnezdenje; Populacijska dinamika; Populacijska gostota; Population Density; Population Dynamics; Ptice; Slovenija